2012
DOI: 10.1016/j.jviromet.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cellular and HPV 16 methylation as biomarkers for cervical neoplasia

Abstract: Aberrant promoter methylation of biologically relevant genes in cervical cancer and uneven CpG distribution within the human papillomavirus 16 (HPV16) enhancer region have been reported. Cervical samples and questionnaires from 151 women screened for cervical cancer in Appalachian Ohio were analyzed. Methylation was measured by bisulfite sequencing in candidate gene sites in ESR1, DCC, p16, and LINE1 elements. Among 89 HPV16-positive women, CpG sites in the E6 promoter and enhancer regions and the L1 region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
0
19
1
Order By: Relevance
“…As for precancerous lesions, we found a low methylation frequency (2%) of the five target CpGs, and normal samples harbored only unmethylated CpGs. Several studies also reported a very low methylation frequency in cervical dysplasia (28,30,32,33,36). This contrasts with the work of Mazumder and collaborators (31), who describe methylated CpG in 50% of LSIL-HSIL.…”
Section: Hpv16 E2bs Hrm-pcr Is a Reliable Methods For Methylation Assementioning
confidence: 80%
See 1 more Smart Citation
“…As for precancerous lesions, we found a low methylation frequency (2%) of the five target CpGs, and normal samples harbored only unmethylated CpGs. Several studies also reported a very low methylation frequency in cervical dysplasia (28,30,32,33,36). This contrasts with the work of Mazumder and collaborators (31), who describe methylated CpG in 50% of LSIL-HSIL.…”
Section: Hpv16 E2bs Hrm-pcr Is a Reliable Methods For Methylation Assementioning
confidence: 80%
“…Some studies reported decreased E2BS methylation during lesion progression (30)(31)(32) or a trend of a lower risk of incident precancerous and cancerous lesions for patients with high E2BS methylation (33,34). On the contrary, methylation of the five CpGs located in the E2BS1 and E2BS2 and Sp1-binding site (Sp1BS) has frequently been associated with cervical cancer (28,29,(35)(36)(37)(38), and a gradual increase in methylation during lesion progression toward cancer has been reported in some studies (29,36,37,39).…”
mentioning
confidence: 99%
“…The methylation level in cervical cancer correlates with HPV16 infection in cervical cells (Patel et al, 2012), and HPV16 virus integration is related to the development of cervical carcinogenesis (Mazumder et al, 2011). In our previous study, the HPV-positive rate reached up to 73.56% in cervical intraepithelial neoplasias and cervical cancer; a study examining the cervical cancer spectrum in Xinjiang Uyghur women demonstrated that HPV16 accounted for the highest proportion in Uyghur cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These tests can be based on the detection of specific types of oncogenic HPV that identify women at a higher cancer risk (e.g., HPV genotypes 16 and 18) (37). However, many other molecular mechanisms associated with HPV infection are necessary for cervical cancer development, such as chromosomal abnormalities, expression of oncogenes, epigenetic regulation (hyper methylation), and apoptotic markers, which cover a large number of potential biomarkers (3840). Molecular tests have been lately under intensive study as a potential alternative and triage tests for cervical cancer screening.…”
Section: Inaccessibility Of Distressed Appalachian Areas For Cervimentioning
confidence: 99%